2006
DOI: 10.1152/physiolgenomics.00052.2006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the stress-responsive adrenocortical axis

Abstract: The underlying genetic components contributing to individual variability in functions of the stress-responsive hypothalamic-pituitary-adrenal (HPA) axis are poorly understood. To determine genetic loci mediating three aspects of the adrenocortical function, we conducted a quantitative trait locus (QTL) analysis in the segregating F2 generation of a Wistar Kyoto (WKY) ϫ Fischer 344 (F344) cross, two inbred rat strains that differ in several HPA axis measures. The following three components of adrenocortical fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 47 publications
3
47
0
1
Order By: Relevance
“…However, several studies in rats have identified QTL for traits potentially related to those studied here. Tame-1 overlaps with earlier identified QTL influencing several anxiety-related traits (TereninaRigaldie et al 2003), rearing behavior (FernandezTeruel et al 2002), and adrenal gland weight (Solberg et al 2006). Tame-2 overlaps with two QTL for activity and anxiety-related behaviors (Terenina-Rigaldie et al 2003; Conti et al 2004).…”
Section: Discussionmentioning
confidence: 63%
“…However, several studies in rats have identified QTL for traits potentially related to those studied here. Tame-1 overlaps with earlier identified QTL influencing several anxiety-related traits (TereninaRigaldie et al 2003), rearing behavior (FernandezTeruel et al 2002), and adrenal gland weight (Solberg et al 2006). Tame-2 overlaps with two QTL for activity and anxiety-related behaviors (Terenina-Rigaldie et al 2003; Conti et al 2004).…”
Section: Discussionmentioning
confidence: 63%
“…The genome scan detected a highly significant quantitative trait locus associated with poststress corticosterone at the SerpinA6/CBG locus. The cDNA sequence analysis of parental strains revealed a Met276Ile mutation in WKY rat identical to that found in the Biobreeding rat strain that exhibits decreased CBG binding affinity for corticosterone (14). More recently, a series of studies conducted in different pig lines confirmed the genetic linkage or genetic association between SerpinA6/CBG locus and basal cortisol levels in pig (1518).…”
Section: Genetic Studies Highlighting the Central Role Of Cbg In Gc Vmentioning
confidence: 82%
“…Some of these physiological measures, such as basal corticosterone levels and adrenal weights, have been studied in WKY rats to genetically map these phenotypes (Solberg et al, 2006), in addition to many behavioral measures we have analyzed in this study, including locomotion in OFT (Baum et al, 2006) and immobility in FST (Solberg et al, 2004). Utilizing genetically distinct F334 rats, these previous studies identified multiple quantitative trait loci (QTL) associated with WKYs' distinct physiological and behavioral phenotypes.…”
Section: Discussionmentioning
confidence: 99%